Biogas Production from Cow Manure - Dewi Artanti Putri; Roy R Saputro; B Budiyono (International Journal of Renewable Energy Development, 2012)
The production of biogas from livestock waste manure in particular is one of the alternative utilization of organic wastes that can be implemented in Indonesia since there is a huge potential of bio-energy in Indonesia. This study utilizes cow manure as the raw material for making biogas and it is coupled with a cow rumen fluid and water. The objective of this study is to determine the effect of manure, rumen, and water composition in biogas production. The research was conducted in anaerobic for 60 days. The composition of manure, water, and the rumen were vary following the variable and ratio; variable A (manure and water); variable B (manure and rumen). The results indicate that the variable A (manure and water) with a 1:3 ratio, and the variable B (manure and rumen) with a 1:2 ratio produced the highest volume of biogas compared to other ratios. The highest biogas production occurred on average at day 23.